Factors affecting customer loyalty in the logistics service industry: A mediating effect of customer satisfaction - Desy Ayu Sekarwati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to analyze the effect of service quality and customer experience on customer loyalty in the logistics service industry, with customer satisfaction as a mediating factor.Method — This research employed a quantitative approach, focusing on the JNE customers residing in Sarirogo Village as the targeted population. To ensure a representative sample, purposive sampling technique was utilized, resulting in a sample size of 100 respondents. The assessment of the external model's validity and dependability was conducted through the application of SmartPLS. The hypotheses were then tested utilizing the model output obtained from SmartPLS..Result — The findings of this research indicate that service quality significantly contributes to enhancing customer satisfaction. Additionally, the study demonstrates a positive association between customer experience and customer satisfaction. Moreover, customer satisfaction plays a crucial role in fostering customer loyalty. However, it is important to note that service quality and customer experience do not directly impact customer loyalty in this study's results. Interestingly, when examining the relationship between service quality and customer loyalty, it becomes evident that customer satisfaction acts as a mediator, effectively influencing the connection between the two factors in a positive manner. Similarly, in the case of the relationship between customer experience and customer loyalty, customer satisfaction also acts as a mediating variable, playing a positive role in linking the independent variable to the dependent variable.Contribution — This study contributes by revealing the impact of service quality and customer experience on customer loyalty mediated by customer satisfaction within the logistics service industry.